“Los factores biológicos y las emociones en el contexto socio educativo” - Caiza Bosmediano, Gesenia Julliet (2021)
Nowadays learning is considered a complex process, so that, if the society changes, the education also changes. For this reason. The educational actors must adapt to the realities, needs and many factors that appear in the teaching-learning process. In that sense. The objective of this investigation is determine the characteristics of biological factors and emotions in the socio-educational context through the narrative descriptions for the strengthen the teaching-learning Process for fifth level students section "A" of “Lic. Jaime Andrade Fabara" Elementary School. The methodology applied is based on the interpretive focus and the inductive method because the priority is to analyze and reflect on the particular of the investigation subjects in real environments. This work is performing from qualitative investigation because it orients towards understanding the biological characteristics and students emotions. In the same way, the techniques used were as follow: the observation and the interview with their relevant instruments such as observation and interview guide. The educational proposal was the design of a short film through a narrative description that it strengthened the teaching-learning process of the students for facilitating the influence understanding of socio-educational context, as well as the ICT use and audiovisual resources. Regarding the results, the identify the influence of biological factors and emotions in the socio-educational context of student because he is a composite biopsychosocial person of a physical and mental structure.